Expert cues: how expert reviewers are perceived online. Issue 4 (10th July 2020) - Naujoks, Anna; Benkenstein, Martin
Abstract : Purpose: The purpose of this paper is to explore different types of source expertise and how they influence perceived message quality. Consumers face the challenge to identify valuable online reviews. Source expertise as a signal of message quality can be displayed differently, depending on website layout, operator and review author. Design/methodology/approach: Two scenario-based experiments were conducted questioning 135 and 275 participants. They investigate the effect of different types of expert reviewers on perceived message quality and also examine the interplay of source expertise and source trustworthiness. Findings: The findings reveal that the different types of expert reviewers differ in perceived expertise and their impact on perceived message quality. Claims of expertise induce the highest perceived expertise compared to the other expert types and non-experts, but are perceived as less trustworthy. Research limitations/implications: Future research should examine the influence of the expert types across different product and service categories and could also include moderating influences that reflect how consumers process expert cues differently. Practical implications: Cues that signal high expertise and high trustworthiness are likely to deliver the most valuable online reviews. This should be incorporated in the website's layout to help consumers find valuable information. Originality/value: The approach of this research is novel in that it undertakes comparisons between three types of expert cues and non-experts. It also addresses the interplay of source expertise and trustworthiness and examines the effect on message quality.